PENGARUH MEDIA PUZZLE HURUF TERHADAP KEMAMPUAN MENGENAL HURUF ANAK USIA 5-6 TAHUN DI TK ADHYAKSA X KUPANG - Putri Nining Karim, Ya; Olga Litna, Kamelia; Yuniati, Yohana; Kale, Sartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of letter puzzle media on the letter recognition ability of children aged 5–6 years at TK Adhyaksa X Kupang. This research employed a quantitative approach using a Pre-Experimental One Group Pretest-Posttest Design. The research sample consisted of 14 children aged 5–6 years. Data were collected using an observation checklist of letter recognition ability. The data were analyzed through prerequisite testing using the Shapiro–Wilk normality test and hypothesis testing using the Paired Sample t-Test with the assistance of SPSS version 27. The results showed that the average score of children's letter recognition ability increased from 71.64 in the pretest to 80.42 in the posttest. The results of the Paired Sample t-Test indicated a significance value of 0.000 < 0.05, meaning that Ha was accepted and H₀ was rejected. Based on these findings, it can be concluded that letter puzzle media has a significant effect on the letter recognition ability of children aged 5–6 years at TK Adhyaksa X Kupang. Keywords: Letter Puzzle Media, Letter Recognition Ability, Children Aged 5–6 Years, Early Childhood Education, TK Adhyaksa X Kupang.